Java Web services architecture - McGovern, James, 1967- (San Francisco : Morgan Kaufmann Publishers, 2003)
Written by industry thought leaders, Java Web Services Architecture is a no-nonsense guide to web services technologies including SOAP, WSDL, UDDI and the JAX APIs. This book is the trusted advisor to systems architects and provides an unbiased look at many of the practical considerations for implementing web services including authorization, encryption, transactions and the future of Web Services. * Covers all the standards, the JAX APIs, transactions, security, and more. * Contains CD with author code and software from BEA, Sun, The Mind Electric, Altova, CapeClear, Systinet, Republica, Iona, Parasoft, Ipedo, and more. * Web enhanced with additional material at http://www.webservicesarchitecture.com.
Web services overview -- Service-oriented architecture -- Component-based service development -- Soap -- WSDL -- UDDI -- ebXML -- Java web service developer pack -- JAXP -- JAX-RPC -- JAXM -- JAXR -- JAXB -- Transaction management -- Security -- Practical considerations -- Future standards.
Includes index.
Keywords: Web services; Java (Computer program language).; Computer architecture; Electronic books